2007
DOI: 10.2134/jeq2006.0207
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Phosphorus Losses from Grassland in Response to Olsen‐P Accumulation

Abstract: The Olsen-P status of grazed grassland (Lolium perenne L.) swards in Northern Ireland was increased over a 5-yr period (March 2000 to February 2005) by applying different rates of P fertilizer (0, 10, 20, 40, or 80 kg P ha(-1) yr(-1)) to assess the relationship between soil P status and P losses in land drainage water and overland flow. Plots (0.2 ha) were hydrologically isolated and artificially drained to v-notch weirs, with flow proportional monitoring of drainage water and overland flow. Annually, the coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…Therefore, by inference, the existing method of field storage of broiler litter (T2) used in Northern Ireland does not increase P transfers from fields. The impact of higher soil P on increased P concentrations in runoff, which was clearly identified in the mixed ANOVA model, is in agreement with what is now a well recognized positive correlation between soil P and P loss in runoff from both arable and grassland soils, and reported in many studies (Vadas et al 2005;Watson et al 2007). …”
Section: Discussionsupporting
confidence: 89%
“…Therefore, by inference, the existing method of field storage of broiler litter (T2) used in Northern Ireland does not increase P transfers from fields. The impact of higher soil P on increased P concentrations in runoff, which was clearly identified in the mixed ANOVA model, is in agreement with what is now a well recognized positive correlation between soil P and P loss in runoff from both arable and grassland soils, and reported in many studies (Vadas et al 2005;Watson et al 2007). …”
Section: Discussionsupporting
confidence: 89%
“…tested in calcareous soils (Leytem et al, 2005). In temperate soils, the labile-Pi (NaHCO 3 -Pi) status of the soil has been shown to directly influence both the total and the dissolved concentration of P in the land drainage waters and overland flow (Watson et al, 2007). In a recent study of calcareous soils receiving high amounts of manure, we observed that the amount of both organic and inorganic labile-P forms did not significantly differ from those found in soils receiving mineral fertilisers (Romanyà and Rovira, 2007).…”
Section: Farming Practices and Soil P Reservesmentioning
confidence: 99%
“…This suggested that under sustained, long term high P fertilizer applications, there is a buildup in soil P level that results in significant higher P loadings at the watershed outlet. Field studies done by others also show that P application to agricultural soils exceeding P uptake by crops leads to P accumulation in soils in the long term, and this accumulation results in higher P loss to water [10,30,31]. Studies also show that it could take up to 10–50 years to see this build up depending on the soil properties, amount of P applied and cropping systems [30].…”
Section: Resultsmentioning
confidence: 99%